The home market effect, regional inequality, and intra-industry reallocations - Gabriel Felbermayr; Benjamin Jung (University of Tübingen, Faculty of Economics and Social Sciences, 2012)
In New Trade Theory models, the larger region hosts an overproportionate share of producers. This Home Market Effect (HME) exacerbates regional income discrepancies caused by trade frictions or technology differences. With homogeneous firms, it requires inter-industry reallocations to emerge. We present a heterogeneous firms single-sector model with fixed market access costs, in which the HME arises exclusively from empirically more relevant intra-industry reallocations. It is magnified by lower trade costs or higher heterogeneity. In contrast to multi-industry models, a more pronounced HME leads to regional income convergence as adjustment of the firm size distribution counteracts the effects of firmentry.
urn:nbn:de:bsz:21-opus-61344
Keywords: F12; R12; 330; Home Market Effect; Regional Inequality; Monopolistic Competition; Heterogeneous Firms; Economic Geography